Development of Nightingale Frontline: a leadership support service for nurses and midwives during the COVID-19 crisis. Issue 4 (3rd February 2022) - Bond, Carmel; Stacey, Gemma; Matheson, Joanne; Westwood, Greta
Abstract : Background: As COVID-19 hit the UK, it was apparent that frontline healthcare workers would be faced with challenges they had never encountered before. The longer-term leadership support needs of nurses and midwives were considered central to how they would psychologically emerge from the COVID-19 response. In response, a national leadership support service for nurse and midwife leadersat all levels, was rapidly established. Methods: A collaborative approach was used, drawing from an established community of healthcare leadership development consultants and senior healthcare leaders. Practical plans for how the service would run were formulated via online meetings, held between February and March 2020. An internal questionnaire was distributed to attendees, requesting demographic data and feedback to capture the perceived impact of the service on leadership. Results: Overall, confidence in leadership ability/skills increased after attending the service; 68.8% of those who completed post-attendance questionnaires reported having learnt new leadership skills and a motivation to facilitate co-consulting sessions for their teams. The service was positively appraised and there were reports of a degree of influence on leadership, and improved confidence after attending. Conclusion: Leadership and well-being support provided by an independent and external organisation can offer a unique and safe forum for reflection and for healthcare leaders to decompress. This requires a sustainable investment to mitigate the predicted impact of the pandemic.